Africa's insurgents : navigating an evolving landscape - Bøås, Morten, 1965-; Dunn, Kevin C., 1967- (Lynne Rienner Publishers, Inc., 2017)
Amid an array of shifting national, regional, and global forces, how have African insurgents managed to adapt and survive? And what differences and similarities can be found, both among the continent's diverse rebellions and guerilla movements and between them and movements elsewhere in the world? Addressing these issues, the authors of Africa's Insurgents explore how new groups are emerging and existing ones changing in response to an evolving landscape.